2012
DOI: 10.4161/cbt.22280
|View full text |Cite
|
Sign up to set email alerts
|

CLCA2, a target of the p53 family, negatively regulates cancer cell migration and invasion

Abstract: The tumor suppressor p53 transcriptionally regulates a number of genes that are involved in cell-cycle inhibition, apoptosis and the maintenance of genetic stability. Recent studies suggest that p53 also contributes to the regulation of cell migration and invasion. Here, we show that human chloride channel accessory-2 (CLCA2) is a target gene of the p53 family (p53, p73 and p63). CLCA2 is induced by DNA damage in a p53-dependent manner. The p53 family proteins activate the CLCA2 promoter by binding directly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…Interestingly, reduced expression of CLCA2 was frequently observed in breast cancer (26). In addition, CLCA2 was shown to play a crucial role in inhibition of cancer cell migration and invasion (27,28). We confirmed by qPCR that CLCA2 expression was substantially elevated after Fra-1 or c-Jun depletion (Fig.…”
Section: Fra-1 and C-jun Common Target Genes Regulating Cell Prolifersupporting
confidence: 71%
“…Interestingly, reduced expression of CLCA2 was frequently observed in breast cancer (26). In addition, CLCA2 was shown to play a crucial role in inhibition of cancer cell migration and invasion (27,28). We confirmed by qPCR that CLCA2 expression was substantially elevated after Fra-1 or c-Jun depletion (Fig.…”
Section: Fra-1 and C-jun Common Target Genes Regulating Cell Prolifersupporting
confidence: 71%
“…So far, the most important reported inductor is TP53. 15,16,21 On the other hand, epigenetic regulation came out as a key factor that represses CLCA2 expression in malignant tissues, 13,15 but how this is regulated is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous microarray study identified several downstream target genes of p53 family proteins (Affymetrix GeneChip, Santa Clara, CA, USA) (NCBI Gene Expression Omnibus database, accession number GSE 13504; https:// www.ncbi.nlm.nih.gov/geo/). (10,11) In the current study, we validated some of these upregulated genes by real-time RT-PCR and immunoblot analyses. One such gene is BRMS1L, a component of the mSin3/histone deacetylase 1 (HDAC1) repressive machinery.…”
Section: Resultsmentioning
confidence: 91%